The promise of participation experiments in participatory governance in Honduras and Guatemala - Altschuler, Daniel; Corrales, Javier; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
To what extent does participation in one particular domain of public life lead to wider participation in other areas? Through the use of an unprecedented survey supported by case studies this book explores how participatory governance in community-managed schools can alter the civic and political behaviour of participants.
Keywords: Science; Science; Science, general